2017
DOI: 10.21608/ejbo.2017.596.1027
|View full text |Cite
|
Sign up to set email alerts
|

Using Moringa olifera Leaf Extract as a Bio-fertilizer for Drought Stress Mitigation of Glycine max L. Plants

Abstract: D ROUGHT is one of a considerable environmental stresses limiting productivity of crops. This work was conducted to investigate the effect of foliar spray of plant leaf extract (Moringa olifera) to alleviate drought stress in Glycine maxplants (cv.Giza 111). Drought caused significant decreases in growth parameters (shoot and root length, fresh and dry weight of shoots and roots) and photosynthetic pigments (chlorophyll a, chlorophyll b, carotenoids and total pigments). In addition, it caused significant incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 24 publications
(25 reference statements)
3
12
0
1
Order By: Relevance
“…The overexpression of SOD has been considered as a vital antidrought mechanism [43], if accompanied by enhanced H 2 O 2 scavenging mechanisms. Hanafy [44] reported significant increase in the activities of enzymatic antioxidants (GR, SOD and APX) in drought stressed soybean. SOD and APX activities were also increased in canola (Brassica napus L.) under drought stress [45].…”
Section: Plos Onementioning
confidence: 99%
“…The overexpression of SOD has been considered as a vital antidrought mechanism [43], if accompanied by enhanced H 2 O 2 scavenging mechanisms. Hanafy [44] reported significant increase in the activities of enzymatic antioxidants (GR, SOD and APX) in drought stressed soybean. SOD and APX activities were also increased in canola (Brassica napus L.) under drought stress [45].…”
Section: Plos Onementioning
confidence: 99%
“…SOD expression plays a vital role against drought stress by scavenging the H 2 O 2 concentration [67]. Hanafy [68] found that under drought, the activity of the enzymatic antioxidants glutathione reductase (GR), SOD and APX was enhanced in soybean and canola [69]. Moreover, in common bean, MLE treatment, both foliar spray and seed priming, significantly increased enzymatic antioxidant activities such as those of GR, SOD and APX [70].…”
Section: Discussionmentioning
confidence: 99%
“…Drought stress has a destructive effect on the cytokinin content of plants; therefore, the high levels of zeatin in MLE make it particularly effective as a natural compound promoting plant tolerance under stress conditions [61]. Hanafy [71] observed that MLE is rich in nutrients, antioxidants (such as ascorbic acid, α-tocopherol, phenols and flavonoids), as well as phytohormones (such as IAA and GAs). Plant growth traits (fresh and dry weights of shoots and roots, shoot and root length) of Glycine max plants were affected by drought and the effect increased as the water holding capacity of the plants decreased (60% and 40%).…”
Section: Effect Of Moringa Oleifera On Plant Growth Characteristics and Yieldmentioning
confidence: 99%